PENGARUH PROFITABILITAS DAN LEVERAGE PADA NILAI PERUSAHAAN DENGAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL MODERASI - Sugiantari, Ni Kadek Dwi Feby; Sisdyani, Eka Ardhani (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2024)
Firm value instability is an interesting phenomenon to study because the firm’s value is related to the company’s performace, shareholder wealth, and business continuity. The research aims to empirically examine the influence of profitability and leverage on firm value with corporate social responsibility disclosure as a moderating variable. This research was conducted on mining companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021. The sampling technique used was a saturated sample and the number of samples used as objects of observation was 199 company data. Moderated Regression Analysis is a data analysis technique used. The research results, it was found profitability had no influence on firm value, leverage had negative influence on firm value, Corporate Social Responsibility Disclosure wasn’t able to moderate d the influence of profitability on firm value, and Corporate Social Responsibility Disclosure was able to moderate d by weakening influence of leverage on firm value.